2019
DOI: 10.18502/npt.v6i3.1256
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between professional autonomy and moral distress in ICU nurses of Guilan University of Medical Sciences in 2017

Abstract: Background & Aim: Professional autonomy is a key component of decision-making and empowerment of the nurses. However, ICU nurses sometimes experience a degree of moral distress in their decision-making but the relationship of this distress with their autonomous performance in intensive care units is unclear. The aim of this study is determining the relationship between professional autonomy and moral distress of ICU nurses. Methods & Materials: In this correlational cross-sectional study, 180 ICU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…It seems that, firstly, having more work experience reduces certain stress-causing factors, and secondly, individuals use different methods to adapt and resolve the intensity of moral challenges. Yeganeh et al found a significant direct relationship between moral distress and the degree of professional autonomy ( 17 ). In this regard, Molloy et al found that one of the most important factors affecting moral distress among NICU nurses is their perception of moral distress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It seems that, firstly, having more work experience reduces certain stress-causing factors, and secondly, individuals use different methods to adapt and resolve the intensity of moral challenges. Yeganeh et al found a significant direct relationship between moral distress and the degree of professional autonomy ( 17 ). In this regard, Molloy et al found that one of the most important factors affecting moral distress among NICU nurses is their perception of moral distress.…”
Section: Discussionmentioning
confidence: 99%
“…In Swedish nurses, low intensity of moral distress was reported ( 16 ). Studies conducted in Iran have indicated moderate to high levels of perceived moral distress among nurses ( 17 - 19 ). In recent years with the advancements in neonatology, perinatology, and infertility treatments, there have been more expectations from the family and treatment team members to help infants survive despite their poor prognosis, being premature, having very low birth weight, and being sick.…”
Section: Introductionmentioning
confidence: 99%
“…Table 2 shows the main characteristics of the included studies. Four studies were conducted in Canada [ 27 , 28 , 29 ], four in Iran [ 30 , 31 , 40 , 41 ], five in the United States of America [ 32 , 33 , 36 , 37 , 38 ], two in Italy [ 11 , 14 ]; one in Israel [ 39 ], and one study was a multi-center study conducted in Croatia, Cyprus, the Netherlands, Slovenia, the United Kingdom, and Belgium [ 34 ]. A total of 16 of the 17 studies had a descriptive cross-sectional design, and only one was a quasi-experimental study [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to the inclusion and exclusion criteria, all included studies used the Moral Distress Scale based on Corley’s theory. Most of them used the Moral Distress Scale–Revised with 21 items [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]; 4 of them used the Moral Distress Scale–Revised with 38 items [ 36 , 37 , 38 , 39 ]; 2 studies used the Moral Distress Scale–Revised with 18 items [ 14 , 40 ]. Lamiani et al [ 11 ] and Asayesh et al [ 41 ] used the Moral Distress Scale–Revised with 14 and 30 items, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation